2019
DOI: 10.3390/sym11101232
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Data Transmission with GSM-MPAPM Modulation for an Indoor VLC System

Abstract: As an emerging wireless communication technique, visible light communication is experiencing a boom in the global communication field, and the dream of accessing to the Internet with light is fast becoming a reality. The objective of this study was to put forward an efficient and theoretical scheme that is based on generalized spatial modulation to reduce the bit error ratio in indoor short-distance visible light communication. The scheme was implemented while using two steps in parallel: (1) The multi-pulse a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…We choose to divide the single bit duration into 4 segments and each segment can transmit 4 bits. Among the previous studies [23] and [24] are closely related to our study. The study in [23], used PWM and PPM in one signal period to represent binary data for 8 constellation points 3 bits can be transmitted.…”
Section: Related Worksupporting
confidence: 77%
See 2 more Smart Citations
“…We choose to divide the single bit duration into 4 segments and each segment can transmit 4 bits. Among the previous studies [23] and [24] are closely related to our study. The study in [23], used PWM and PPM in one signal period to represent binary data for 8 constellation points 3 bits can be transmitted.…”
Section: Related Worksupporting
confidence: 77%
“…Authors employed DPAM for keeping the LED luminous flux constant in each signal period. In [24], the authors proposed a generalized spatial modulation with multi-pulse amplitude and position modulation. Multiple pulse position modulation and pulse amplitude first used to make the transmission signal and then specific LEDs are chosen to transmit data.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Bao et al reported "An Efficient Data Transmission with GSM-MPAPM Modulation for an Indoor VLC System" [14]. The objective of this study was to put forward an efficient and theoretical scheme that is based on generalized spatial modulation to reduce the bit error ratio in indoor short-distance visible light communication.…”
Section: Lan Et Al Reported "Symmetric Modeling Of Communication Effectiveness and Satisfactionmentioning
confidence: 99%
“…To further enhance the system performance, the advantages of M-PPM and M-PAM are combined in multiple pulse amplitude and position modulation (M-PAPM) [25]. Alternatively, various modulation formats with different hybrid approaches for OWC system have been proposed over the years [26][27][28][29][30][31][32][33][34]. Hybrid modulation techniques can simultaneously transmit higher data with both high spectral and power efficiencies over traditional modulation techniques [29].…”
Section: Introductionmentioning
confidence: 99%